Superspin glass behavior of a nonstoichiometric lanthanum manganite LaMnO3.13 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
Aging and memory effects are observed in an oxygen nonstoichiometric lanthanum manganite LaMnO3.13 from time-dependent dc magnetic measurements by employing various cooling protocols. The results can be best described by the superspin glass model of interacting magnetic nanoparticles system. The possible origin of such a behavior is the confinement of interacting small magnetic clusters formed as a result of the formation of manganese vacancies, along with the random distribution of tetravalent manganese ions in the lattice.

Synthesis and magnetic properties of polycrystalline Co-doped ZnO - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline Zn1-xCoxO powders have been synthesized by a glycine-nitrate (GNP) and modified GNP methods. Ferromagnetism at room temperature and above is observed for the powder samples synthesized by GNP method. The saturation magnetization value at 300 K is obtained as 0.08 and 0.28 emu/g (at 1 T), respectively, for x = 0.05 and 0.1. Ferromagnetic transition occurs at 740 K and 770 K for the respective samples, which is much larger than that the reported in the literature for thin film samples. On the other hand, no ferromagnetism was observed, down to 10 K, for the compounds synthesized by the modified GNP method.

Synthesis of chromium substituted nano particles of cobalt zinc ferrites by coprecipitation - Sharma, R. K.; Suwalka, O.; Lakshmi, N.; Venugopalan, K.; Banerjee, Abhik; Joy, Pattayil Alias (Materials Letters, 2005)
Nano particles of chromium substituted cobalt zinc ferrite have been synthesized by a chemical co-precipitation method. X-ray diffraction studies of the nano particles of CrxCo0.5-xZn0.5Fe2O4 (x = 0.1 to 0.5) heat-treated at 300 degrees C show that the particle sizes are in the range of 2 to 7 nm. Room temperature Fe-57 Mossbauer spectra of all the samples show only two doublets, confirming the presence of superparamagnetic relaxation in the nano particles. An exponential decrease in the superparamagnetic blocking temperature, with increasing chromium concentration, is observed for these samples. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Co0.5Zn0.5Fe2O4; Mossbauer spectroscopy; nano materials

Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Synthesis and magnetic properties of Mn doped ZnO nanowires - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2007)
Mn doped ZnO nanowires have been synthesized using a simple autocombustion method. The as-synthesized Mn doped ZnO nanowires were characterized by X-ray diffraction and transmission electron microscopy. An increase in the hexagonal lattice parameters of ZnO is observed on increasing the Mn concentration. Optical absorption studies show an increment in the band gap with increasing Mn content, and also give evidence for the presence of Mn2+ ions in tetrahedral sites. All Zn1-xMnxO (0 <= x <= 0.25) samples are paramagnetic at room temperature. However, a large increase in the magnetization is observed below 50 K. This behavior, along with the negative value of the Weiss constant obtained from the linear fit to the susceptibility data below room temperature, indicate ferrimagnetic behavior. The origin of ferrimagnetism is likely to be either the intrinsic characteristics of the Mn doped samples, or due to some spinel-type impurity phases present in the samples that could not be detected. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; diluted magnetic semiconductor; magnetic properties; Mn doped ZnO

Size dependent coordination behavior and cation distribution in MgAl2O4 nanoparticles from Al-27 solid state NMR studies - Sreeja, V.; Smitha, T. S.; Nand, Deepak; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Journal of Physical Chemistry C, 2008)
Nanoparticles of spinel-type oxides such as ferrites offer great advantages and applications in many important areas. Decreasing the size of the particles to nanometer size will increase the surface-to-volume ratio and this will strongly influence the physical and chemical properties of these materials. For magnetic nanoparticles, the exchange interactions at the surface of a particle will be different from those inside due to changes in the coordination behavior at the surface. Therefore, studying and understanding the coordination and distribution behavior of the different metal ions in the nanoparticles of spinel-type oxides is very important. Solid state NMR is a useful and important technique to obtain information on local structural variations. The degree of the distribution of the Al3+ ions in the tetrahedral and octahedral sites in the nanoparticles of the nonmagnetic spinet MgAl2O4 having different particle sizes has been determined by Al-27 magic-angle spinning (MAS) NMR spectroscopy. It has been observed that the inversion parameter decreases with increasing particle size. Apart from the usual tetrahedral and octahedral coordinations present in the bulk material, the presence of five- and three-coordinated At has been observed in nanoparticles with sizes less than 18 nm and a second octahedral coordination is observed for nanoparticles of larger sizes.

Superparamagnetic nanocrystalline ZnFe2O4 with a very high curie temperature - Deka, Sasanka; Joy, Pattayil Alias (Journal of Nanoscience and Nanotechnology, 2008)
Studies on the magnetic properties of nanocrystalline ZnFe2O4 synthesized by an autocombustion method are reported. Superparamagnetic behavior is observed for the nanocrystalline materials with particle sizes of 8 nm and 17 nm, with superparamagnetic blocking temperatures of 65 K and 75 K, respectively. Magnetic hysteresis with very large coercivities of 533 Oe and 325 Oe, respectively, are observed at 12 K. Studies on the temperature variation of the magnetization above room temperature indicate that the Curie temperature is as high as similar to 800 K when compared to the paramagnetic nature of bulk zinc ferrite at room temperature.
Keywords: Curie temperature; Nanocrystalline; Superparamagnetism; Zinc Ferrite

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Solid state synthesis and room temperature magnetic properties of iron phosphide nanoparticles - Singh, N.; Khanna, P. K.; Joy, Pattayil Alias (Journal of Nanoparticle Research, 2009)
Room temperature magnetic properties have been achieved for nano-crystalline iron phosphide synthesized from the direct solid state reaction of iron chloride and tri-octylphosphine (TOP). The magnetization continuously increased with higher magnetic fields, indicating a super-paramagnetic behavior. It is observed that room temperature magnetism is possible for the material showing antiferromagnetic nature at low temperatures. In the present synthesis, TOP acted as a source of phosphorus as well as a surfactant. X-ray diffraction (XRD) studies revealed that the black powder is a mixture of FeP and Fe(2)P. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed elongated as well spherical particles. Energy dispersion X-ray analysis (EDAX) confirmed a non-stoichiometric iron phosphide. Presence of TOP was confirmed by infra-red (IR) spectroscopy, and thermo-gravimetric analysis (TGA) indicated about 6% wt. loss due to presence of organics.
Keywords: Iron phosphide; Semiconductors; Solid state reaction; synthesis; XRD

On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction

Superparamagnetic nanocomposite of magnetite and activated carbon for removal of dyes from waste water - Thakuria, Pankaj; Joy, Pattayil Alias (Nanoscience and Nanotechnology Letters, 2009)
Nanocomposite of superparamagnetic Fe(3)O(4) and activated carbon (AC) is synthesized at room temperature and characterized by various techniques. Magnetic measurements indicated that the Fe(3)O(4) nanoparticles are isolated by the AC particles. The magnetic fluid obtained by dispersion of the nanocomposite in water is found to be relatively stable. The dispersion is found to be very efficient for the removal of methylene blue dye from water. Thus, the nanocomposite is highly suitable for removing dissolved dyes and other contaminants from waste water by a simple magnetic separation process after adsorption on AC.
Keywords: Magnetic Separation; Nanocomposite; Superparamagnetism; Water Purification

Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites

Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering

Synthesis of bio-compatible SPION-based aqueous ferrofluids and evaluation of radiofrequency power loss for magnetic hyperthermia - Mary, Antony P. Reena; Narayanan, T. N.; Sunny, Vijutha; Sakthikumar, D.; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Bio-compatible magnetic fluids having high saturation magnetization find immense applications in various biomedical fields. Aqueous ferrofluids of superparamagnetic iron oxide nanoparticles with narrow size distribution, high shelf life and good stability is realized by controlled chemical co-precipitation process. The crystal structure is verified by X-ray diffraction technique. Particle sizes are evaluated by employing Transmission electron microscopy. Room temperature and low-temperature magnetic measurements were carried out with Superconducting Quantum Interference Device. The fluid exhibits good magnetic response even at very high dilution (6.28 mg/cc). This is an advantage for biomedical applications, since only a small amount of iron is to be metabolised by body organs. Magnetic field induced transmission measurements carried out at photon energy of diode laser (670 nm) exhibited excellent linear dichroism. Based on the structural and magnetic measurements, the power loss for the magnetic nanoparticles under study is evaluated over a range of radiofrequencies.
Keywords: Magnetic heating; Magnetic hyperthermia; Magnetic relaxation; Power loss; Superparamagnetism

Structural, magnetic and mossbauer spectral studies of nanocrystalline Ni0.5Zn0.5Fe2O4 ferrite powders - Verma, Seema; Joy, Pattayil Alias; Kurian, Sajith (Journal of Alloys and Compounds, 2011)
Nanocrystalline Ni0.5Zn0.5Fe2O4 powders, synthesized by a combustion method are investigated by X-ray diffraction, vibrating sample magnetometry and Mossbauer spectroscopic techniques. We adopt a strategy to systematically control the particle sizes between 4 and 45 nm simply by changing the elemental stoichiometric coefficient, Phi(e), of the combustion mixture. Curie temperature of the superparamagnetic particles of size 4 nm is higher than that of the bulk particles. Interestingly, bigger particles (45 nm) show a comparable room temperature saturation magnetization and exceptionally very high Curie temperature of 833 K, when compared to that of the bulk Ni0.5Zn0.5Fe2O4 material (563 K). (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Chemical synthesis; Magnetisation; Mossbauer spectroscopy; Nanostructured materials

Studies on the effect of sintering conditions on the magnetostriction characteristics of cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of the European Ceramic Society, 2014)
The effect of sintering conditions on the magnetostriction characteristics of sintered cobalt ferrite derived from nanocrystalline powders is studied. It is observed that the magnetostriction coefficient as well as the slope of the magnetostriction as a function of field depends on the microstructure of the sintered product. There is a direct correlation between the magnetostriction characteristics and density as well as porosity of the sintered products. Intragranular pores are found to be strongly influencing the magnetostriction characteristics. Similarly, correlation is found between the magnetostriction parameters and the Curie temperature, indicating the role of cation distribution which affects the magnetic anisotropy. Sintering the compacts made from nanocrystalline powders at 1450 degrees C for a very short duration is found to give high values of magnetostriction coefficient. However, higher values of magnetostriction at low magnetic fields are obtained for samples sintered at lower temperatures for longer duration and having relatively lower density. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Microstructure; Nanocrystalline; Sintering

Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance

Studies on the role of unsaturation in the fatty acid surfactant molecule on the thermal conductivity of magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of colloid and interface science, 2017)
To study the role of unsaturation in the surfactant molecule on the thermal conductivity of magnetite nanofluids, four different fatty acid (stearic, oleic, linoleic, and linolenic acids with different degree of unsaturation) coated magnetite nanoparticles of comparable size are prepared and dispersed in toluene. It is found that the nanofluid with the saturated fatty acid coated nanoparticles show larger viscosity than the fluid with the unsaturated fatty acid coated particles at all concentrations. Thermal conductivity studies show enhancement only above a critical concentration for all fluids. The critical concentration for thermal conductivity enhancement varies with the surfactant, possibly due to the difference in the degree of aggregation of the nanoparticles in the fluid, because of the difference in the conformation of the surfactant molecules on the nanoparticle's surface. The experimental thermal conductivity follows the Maxwell model at higher concentrations. From the overall studies, it is observed that the thermal conductivity of the fluids with aggregated or assembled nanoparticles shows slightly larger enhancement than that of the fluids with isolated particles. However, in the presence of a magnetic field, the fluids with isolated nanoparticles showed relatively larger enhancement, possibly due to the easy response of the isolated magnetite nanoparticles to the applied field. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Chains; Dynamics; Enhancement; Fields; Fluids; Forces; gold nanoparticles; Magnetic fluid; Nanofluid; Surfactant; Unsaturation; Conformation; Thermal conductivity; Viscosity; Self-assembled Monolayers

Spin state engineered ZnxCo3-xO4 as an efficient oxygen evolution electrocatalyst - Ramsundar, Rani Mohan; Pillai, Vijayamohanan Kunjukrishna; Joy, Pattayil Alias (Physical Chemistry Chemuical Physics, 2018)
Oxygen evolution is the key step in the oxidation of water in electrolyzers and photoelectrochemical cells for the production of hydrogen. Developing a non-precious metal oxide catalyst with good electrocatalytic activity for the oxygen evolution reaction (OER) is very challenging. In this work, nanostructured ZnxCo3-xO4 has been shown as an efficient catalyst with a low overpotential for the OER in 0.1 M KOH solution. Substitution of Co2+ in the spinel oxide Co3O4 with Zn2+ creates a higher number of high-spin Co3+, which is found to be directly correlated with the OER activity of ZnxCo3-xO4. Zn0.8Co2.2O4 (x = 0.8) with the optimum amount of Co2+/Co3+ and high-spin Co3+ content showed a very low overpotential of approximate to 250 mV, at 10 mA cm(-2), with a turnover frequency of approximate to 3 x 10(-3) s(-1) for the OER. The high Faradaic efficiency along with the stability of Zn0.8Co2.2O4 and electrocatalytic activity comparable with that of precious metal oxides indicate that this composition is a promising catalyst for water oxidation.

Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals